Communicating compassion in organizations: a conceptual review - McAllum, Kirstie; Fox, Stephanie; Ford, Jessica L.; Roeder, Arden C. (Frontiers in Communication, 2023)
This article explores the theoretical terrain surrounding compassion in organizational settings to clarify how conceptually (dis)similar concepts like social support, team care, and organizational compassion manifest different agentic perspectives on compassion. Toward this end, we articulate a working definition of compassion and suggest that a communicative frame focused on intersubjective sense-making and interpretation can deepen our understanding of who is responsible for care and compassion within organizations. Existing research on this subject considers who or what provides compassion-individuals, teams, policies-and how compassion can assuage suffering and promote individual and organizational flourishing. Extending this work, we document core dimensions of each form of compassion for greater conceptual clarity and precision, proposing a metaphor for each.Finally, we reflect on the implications of each type of compassion for resilience and the ways current notions of compassion typify the rationality/emotionality duality and gendered nature of emotion work in organizations.